Proceedings of the 35th Annual Hawaii International Conference on System Sciences
DOI: 10.1109/hicss.2002.994259
|View full text |Cite
|
Sign up to set email alerts
|

Market segmentation and information development costs in a two-tiered fee-based and sponsored-based web site

Abstract: We develop an analytical model of a separating equilibrium for a two-tier fee-based and sponsored-based information Web site. We examine the monopolist' s choice of content quality and price for a fee-based site targeted at high type consumers and the content quality level for a sponsored site offered free to all consumers. We show how a reduction in the potential for advertising revenues results in lower content quality on the free site, but permits the seller to raise the fee charged to high type consumers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Several scholars (e.g., Bourreau 2003, Dukes 2004, Dukes and Gal-Or 2003, Masson et al 1990, Nilssen and Sørgard 2001, Peitz and Valletti 2008, Spence and Owen 1977 have studied the ad-sponsored model in reference to TV commercials. Further, Riggins (2002) studied the case in which a monopolist offers an ad-sponsored website to both high-and low-type consumers and a fee-based portion to high-type consumers only. Gabszewicz et al (2006) found that advertisements may increase or decrease the product price depending on the customers' attitude towards advertisements.…”
Section: Ad-sponsored Business Modelmentioning
confidence: 99%
“…Several scholars (e.g., Bourreau 2003, Dukes 2004, Dukes and Gal-Or 2003, Masson et al 1990, Nilssen and Sørgard 2001, Peitz and Valletti 2008, Spence and Owen 1977 have studied the ad-sponsored model in reference to TV commercials. Further, Riggins (2002) studied the case in which a monopolist offers an ad-sponsored website to both high-and low-type consumers and a fee-based portion to high-type consumers only. Gabszewicz et al (2006) found that advertisements may increase or decrease the product price depending on the customers' attitude towards advertisements.…”
Section: Ad-sponsored Business Modelmentioning
confidence: 99%
“…The above research tends to see content and advertising as a whole and bases versioning on the ad volume alone, whereas, in practice, platforms tend to base versioning on the content quality and the ad volume, which receives scant academic attention. For example, Riggins (2002) studied an information Web site's choice of the content quality and price level for a fee‐based site and the degraded quality level for a sponsored site and showed that a reduction in the potential for advertising revenues results in lower content quality on the free site but permits the seller to raise the fee charged to high‐type consumers. Halbheer et al (2014) developed an analytical framework to study sampling strategies (lower‐end version with advertisements is offered for free and consumers need to pay for access to the higher‐end version) for online publishers of information goods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other scholars also take the quality difference into consideration when studying the vertical differentiation strategy in two‐sided markets, such as Riggins (2002), Halbheer et al (2014), and Wang et al (2021). However, all of them assumed that there is a free lower‐quality product with advertisements and seldom considered how to price advertising.…”
Section: Introductionmentioning
confidence: 99%
“…Viewers have to view ads that come in order to access the free product. To mirror the properties of pricing and advertising strategies, let the cost of setting ads be zero [7], and the producing cost of content is negligible on Internet.…”
Section: The Modelmentioning
confidence: 99%
“…With significant increasing number of the Internet users, the pricing and advertising models have attracted attention of many researchers. Riggins [7] develops a separating equilibrium model for fee-based and ads sponsored-based websites and examines a monopolist's choice of web content price and quality. In another study, Prasad et al [8] suggest different optimal strategies for content firms depending on the context: pure pay-per-view strategy for high income users, who are willing to pay the advertising avoidance fee, and free strategy based on advertisement for high advertising sales with low-quality content.…”
Section: Introductionmentioning
confidence: 99%